COMPARISON OF PROTECTIVE EFFECT OF GREEN TEA AND VITAMIN C AGAINST CYPERMETHRIN INDUCE NEPHROTOXICITY IN MICE - Manzoor, Saima; Mehboob, Khadija; Naveed, Abdul Khaliq (Journal of Ayub Medical College Abbottabad, 2016)
Background Insecticide toxicity is the problem of every person in under developed countries. It is necessary to counteract its effect by natural and cheap remedies like green tea and vitamin C. In this manner common man can also enjoy blessings of life. The current research was performed to compare the protective function of green tea and vitamin C on experimental cypermethrin provoked nephrotoxicity Method: Forty healthy Balb/C mice purchased from National Institute of Health, Islamabad, Pakistan and divided in to four groups (10 each). Group a was control which received only normal diet. Group B, group C and group D were experimental groups which were given Cypermethrin, Cypermethrin with green tea and Cypermethrin with vitamin C respectively. These groups were also given normal diet. After 1 month blood was drawn by intra-cardiac method to assess renal parameters. Results: One month research showed increase in serum urea to 6.8±.48 m.mol/l (n=3.9±.44) while green tea and vitamin C normalize them to 4.0±.83m.mol/l and 3.4±.33m.mol/l respectively. Serum creatinine increased to 42.90±3.28m.mol/l (n=29.50±3.95) while green tea and vitamin C normalize them to 28.80±4.58m.mol/l and 22.60±2.06m.mol/l correspondingly. Conclusion The results showed that green tea and vitamin C neutralized toxicity induced by Cypermethrin in mice and their effect is comparable. Keywords: Cypermethrin, serum urea, serum creatinine, green tea, vitamin C